Designing an Organization for Innovation in Emerging Economies: the Mediating Role of Readiness for Innovation - Arshi, Tahseen; Burns, Paul (Organizations and Markets in Emerging Economies, 2019)
The study proposes an organizational design framework that impacts innovation in corporate firms. In an emerging economy like Oman, innovation helps to reduce the dependence on oil revenues and enhance its international competitiveness. However, the corporate organizations in emerging economies are unable to innovate effectively because they are not designed for innovation. Further, scarcity of resources undermines their readiness for innovation. This study empirically validates measures of an entrepreneurial organizational design framework in Omani corporate sector. In order to explain how a corporate organizational design promotes innovation and clarify the missing links between corporate entrepreneurial activity and innovation, the mediating role of readiness for innovation (RFI) is tested. Using a quantitative research approach, data is collected from 401 corporate firms in Oman and analysed using structural equation modelling. The findings support the proposition that entrepreneurial organizational design promotes both radical and incremental innovation degree and frequency, while RFI partially mediates the relationship between entrepreneurial inputs and innovation outputs. The study contributes to the understanding of innovation in emerging economies as it explains that RFI helps firms to enhance its innovation potential by optimizing its resources, capabilities and processes for innovation. These measures are essential for organizations, particularly in emerging economies focused on low cost innovation. The findings of the study will inform managerial decision-making in terms of designing organizations for innovation and implementation of measures related to readiness for innovation.